Zoonoses Anticipation and Preparedness Initiative, stakeholders conference, February 4 & 5, 2021. (November 2021) - Beer, Martin; Amery, Leanne; Bosch, Berend-Jan; Brix, Alexander; Daramola, Olalekan; Inman, Sophie; Jungbäck, Carmen; Kortekaas, Jeroen; Lindo, Viv; Okorji-Obike, Uche; Rodriguez-Conde, Sara; Tang, Alison; et al.
Abstract: The Zoonoses Anticipation and Preparedness Initiative (ZAPI) was set up to prepare for future outbreaks and to develop and implement new technologies to accelerate development and manufacturing of vaccines and monoclonal antibodies. To be able to achieve surge capacity, an easy deployment and production at multiple sites is needed. This requires a straightforward manufacturing system with a limited number of steps in upstream and downstream processes, a minimum number of in vitro Quality Control assays, and robust and consistent platforms. Three viruses were selected as prototypes: Middle East Respiratory Syndrome (MERS) coronavirus, Rift Valley fever virus, and Schmallenberg virus. Selected antibodies against the viral surface antigens were manufactured by transient gene expression in Chinese Hamster Ovary (CHO) cells, scaling up to 200 L. For vaccine production, viral antigens were fused to multimeric protein scaffold particles using the SpyCatcher/SpyTag system. In vivo models demonstrated the efficacy of both antibodies and vaccines. The final step in speeding up vaccine (and antibody) development is the regulatory appraisal of new platform technologies. Towards this end, within ZAPI, a Platform Master File (PfMF) was developed, as part of a licensing dossier, to facilitate and accelerate the scientific assessment by avoiding repeated discussion of already accepted platforms. The veterinary PfMF was accepted, whereas the human PfMF is currently under review by the European Medicines Agency, aiming for publication of the guideline by January 2022. Highlights: Combinations of single-domain antibodies targeting different sites resulted in very potent neutralization activity. Bacterial superglue was highly efficient for manufacturing consistent particle-display vaccine complexes. The C1 fungus-based expression system was significantly improved and delivered viral antigen subunits at high yields. Candidate vaccines were validated in target species, showing protective immunity. A Platform Master File accelerates scientific assessment by avoiding repeated discussion of already accepted platforms.